National Health Service : deputation to Minister of Health on 17 June 1946 (report) - Bevan, Aneurin, 1897-1960
1946-06-25 1946 1940s 9 pages -8- the Regional Board under the direction of the Minister to deal with the remuneration and conditions of service of all officers of hospitals. He was anxious to use existing machinery for remuneration. The individual employees would be in contract with the Regional Board - they did not want them to be in contract with the Minister. Overweighting of Regional Board by Doctors This Board, he said, should be a body of persons appointed because of their knowledge of hospital administration. Local health officers and trade unions in the area would be consulted. He said that he did not want the tenure of office of the Regional Board laid down in the Bill, but to be dealt with by regulations. Hospital Management Committees He wanted the representation on those committees to be as localised as possible. He thought it would be rather difficult to determine how the selection was to be made. The Regional Board broke itself down into Hospital Management Committees. The Board had no detailed administration inside hospitals. That was the function of the Hospital Management Committees and House Committees. After the Regional Board had made its plans it would have far less day to day work than Hospital Management Committees. This was not actually specified in the Bill as they were anxious to be free to appoint a particular Management Committee suitable to the nature of the hospitals e.g. Jewish and Catholic Hospitals. Superannuation They wanted to provide as much mobility in the service as possible. In that way only was there possibility of promotion. There should be a superannuation scheme by which the benefits could be carried on. MR. BULLOCK said that the present hospital clientele was fairly mobile. Comparison should be made between ordinary and mental hospital work. The weight of the duties in the mental ward might be so arduous that a person was likely to die much earlier. How was it intended to merge the various schemes in operation at present where in some cases some people retired at 55? MR. BEVAN said that where special advantages had been obtained they would be carried over into the new scheme. MR. ALLEN asked whether the Minister said that in spite of the provisions in the National Insurance Bill. There was something that was often too readily missed. At the same time as talking about people retiring at 55, there was another measure in which people continued working until 65 or otherwise came under a different class of insurance. DR. MORGAN said that there were certain officers now employed by local authorities who would still remain temporary in the employment of local authorities but who would have their work diminished. Some of their functions would be transferred to the new service. MR. BEVAN said that where the work was directly affected they would be compensated. The Government could not, however, keep on compensating people for the indirect consequences of state action. 292/847/4/113